PEMBUKTIAN TERHADAP TINDAK PIDANA PENGHINAAN DALAM KONTEN YOUTUBE PADA PUTUSAN PENGADILAN JAKARTA SELATAN (STUDI KASUS PUTUSAN NOMOR 1327/PID.SUS/2019/PN JKT.SEL) - Rizky Setiawan; Ade Adhari (Jurnal Hukum Adigama, 2022)
The use of Youtube social media is often misused or unwittingly the content uploaded contains criminal acts. As in the case of "salted fish" Decision Number 1327/Pid.Sus/2019/Pn Jkt.Sel which contains elements of humiliation. The problem arises, how is the application of evidence against criminal acts of humiliation through Youtube social media in the case of decision Number 1327/Pid.Sus/2019/Pn Jkt.Sel? The normative juridical research method uses deductive data analysis techniques. The application of evidence still refers to Article 184 of the Criminal Procedure Code. The evidence submitted was the testimony of witnesses including victim witnesses, information from ITE experts and criminal law experts, as well as statements from the defendants. For evidence, namely electronic devices and print outs. The indictment of Article 27 paragraph (1) the prosecutor could not prove a violation of decency so that the judge chose the primary alternative indictment Article 27 paragraph (3) was proven as a criminal offense and the perpetrators were qualified as "people who participated in the act" (medepleger). The government and the legislature need to revise the ITE Law because there are many articles that have multiple interpretations.